ANIMAL WELFARE CONCERNS AT A FISH FARMING OPERATION IN SOUTHEASTERN BRAZIL - Rodrigues, Diego André; Carleti Junior, Alberto Geraldo; Balista, Wagner Cezario; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2015)
Concern for the welfare of the fish during the production process is not very common among consumers and producers as suggested by the scant literature on the subject, more specifically in the area of animal welfare (Benson & Rollin, 2004; Carneiro et al., 2007). However, this scenario is gradually changing, with increasing international publications, reports and books devoted to the welfare of fish (Erickson, 2003; Pedrazzani et al., 2007; Volpato, 2007). This study focuses on demonstrating what the members of an association of fishermen (who grow tilapia and robalo-peva) think about sentience and fish welfare at slaughter. This will help us determine if the topic is being considered during the commercial production of fish.